2022
DOI: 10.1186/s11658-022-00408-7
|View full text |Cite
|
Sign up to set email alerts
|

The transition from HIF-1 to HIF-2 during prolonged hypoxia results from reactivation of PHDs and HIF1A mRNA instability

Abstract: The hypoxia-inducible factors (HIF) are transcription factors that activate the adaptive hypoxic response when oxygen levels are low. The HIF transcriptional program increases oxygen delivery by inducing angiogenesis and by promoting metabolic reprograming that favors glycolysis. The two major HIFs, HIF-1 and HIF-2, mediate this response during prolonged hypoxia in an overlapping and sequential fashion that is referred to as the HIF switch. Both HIF proteins consist of an unstable alpha chain and a stable beta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 57 publications
1
36
0
1
Order By: Relevance
“…In contrast, a 4 hour incubation with permanent hypoxia of 1% of oxygen clearly induced HIF stabilization. Our data are in line with different publications showing that various other cell types similarly require lower oxygen concentrations or prolonged exposure in order to mediate HIF1α and HIF2α accumulation in a time-dependent manner ( Bracken et al, 2006 ; Bartoszewski et al, 2019 ; Jaskiewicz et al, 2022 ). From a translational perspective, it needs to be considered that coronary artery endothelial cells are not exposed to such low oxygen concentrations during OSA desaturations further underlining the need for more physiological OSA models.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a 4 hour incubation with permanent hypoxia of 1% of oxygen clearly induced HIF stabilization. Our data are in line with different publications showing that various other cell types similarly require lower oxygen concentrations or prolonged exposure in order to mediate HIF1α and HIF2α accumulation in a time-dependent manner ( Bracken et al, 2006 ; Bartoszewski et al, 2019 ; Jaskiewicz et al, 2022 ). From a translational perspective, it needs to be considered that coronary artery endothelial cells are not exposed to such low oxygen concentrations during OSA desaturations further underlining the need for more physiological OSA models.…”
Section: Discussionsupporting
confidence: 92%
“…( 54 ) In this study, Hif2a mRNA levels were twofold higher than Hif1a under normoxia and were fivefold higher during chronic hypoxia (24 hours). ( 54 ) Time‐course mRNA studies on human endothelial cells under hypoxia revealed that differences in Hif1a and Hif2a mRNA levels were the result of microRNA destabilization of the adenylate‐uridylate‐rich element (ARE) at the 3' end of Hif1a and Hif2a transcript untranslated region. The Hif1a 3' UTR is highly sensitive to ARE‐dependent destabilization compared with the 3' UTR of Hif2a .…”
Section: Hif Isoform Functionmentioning
confidence: 54%
“…( 52 , 53 ) In human umbilical vein endothelial cells (HUVECs) exposed to hypoxia, HIF‐1α rapidly accumulates during acute hypoxia (4 hours), reduces during the acute‐chronic hypoxia transition (8 hours), and drastically reduces thereafter during chronic hypoxia exposure (24 hours). ( 54 , 55 ) HIF‐2α levels reach a peak during the acute‐chronic hypoxia transition (8 hours) and are sustained during chronic hypoxia exposure (24 hours). ( 54 , 55 ) Hif1a mRNA levels were reduced post‐HIF‐1α peak (at 8 hours), whereas Hif2a mRNA levels were sustained at higher levels throughout the time course.…”
Section: Hif Isoform Functionmentioning
confidence: 99%
See 2 more Smart Citations